Legality of Qiyas in Legal Terms: The Implementation in Islamic Economics and Finance - Muhammad Baharudin Syah; Muhajirin Muhajirin (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThis study seeks to analyze in more depth and specifics how al-Shafi'i's biography and the epistimology of his fiqh, ijtihad and istinbath, how the development of qiyas and his thinking changed from qaul qodim to qaul jadid, and how his thought was implemented in the field of sharia economics and finance. The method used in this study is a descriptive qualitative approach using data collection methods in the form of librarianship or literature review. This type of research is research. The implementation of the Qiyas method in the field of sharia economics and finance is as in sharia law, which is very relevant to the concept of shirkah according to Indonesian law, the prohibition of selling and buying orders (salam) online with a mystery box, the legal validity of the legal agreement/transaction of buying and selling via digital messages or similar communication media, and the equalization of zakat distribution to asnaf zakat.Keywords: Imam Syafi’i, Islamic Economy, Islamic Sharia, Qaul Jadid, Qaul Qadim. AbstrakPenelitian ini berupaya membedah lebih dalam dan spesifik tentang bagaimana biografi al-Syafi’i dan dasar epistimologi fiqihnya, ijtihad dan istinbath-nya, bagaimana pengembangan qiyas dan perubahan pemikirannya dari qaul qodim menuju qaul jadid, dan bagaimana implementasi pemikiran beliau dalam bidang ekonomi dan keuangan syariah. Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif deskriptif dengan menggunakan metode pengumpulan data berupa kepustakaan atau literature review. Sedangkan jenis penelitian ini adalah penelitian. Implementasi metode Qiyas dalam bidang ekonomi dan keuangan syariah adalah seperti dalam akad syirkah yang sangat relevan dengan konsep syirkah sesuai UU di Indonesia, larangan jual beli pesanan (salam) secara online dengan mystery box, keabsahan hukum akad/transaksi wakalah jual beli melalui via pesan digital atau media komunikasi sejenisnya, dan penyamarataan pembagian zakat kepada asnaf zakat.Kata kunci: Ekonomi Islam, Imam Syafi’i, Qaul Jadid, Qaul Qadim, Syariah Islam.